Learn!Bio—A time-limited cross-sectional study on biosciences students’ pathway to resilience during and post the Covid-19 pandemic at a UK university from 2020–2023 and insights into future teaching approaches - Katy Andrews; Rosalie Stoneley; Katja Eckl (PLoS ONE, 2025)
Higher education in biosciences is substantiallyinformed by hands-on field trips and practical laboratory skills-training. With the first Covid-19 national lock-down in England in March 2020, on-campus education at higher education institutions was swiftly moved to alternative provisions, including online only options, a mix of synchronous or asynchronous blended, or hybrid adaptions. Students enrolled on an undergraduate bioscience programme have been faced with unprecedented changes and interruptions to their education. This study aimed to evaluate bioscience students’ ability to adjust to a fast-evolving learning environment and to capture students’ journey building up resilience and graduate attributes. A total of 317 Bioscience undergraduate students in years 1–3 at the biology department at a northwest English university participated in this anonymous, cross-sectional, mixed-method study with open and closed questions evaluating their perception and feedback to remote and blended learning provisions during the Covid-19 pandemic and post pandemic learning capturing academic years 2019/20–2022/23. The Covid-19 pandemic and the consequent restriction of personal social interaction resulted in an significant decrease in the mental wellbeing of undergraduate bioscience students in this study, cumulating in poor or very poor self-rating of wellbeing in spring 2021; while at the same time students showed evidence of advanced adaption to the new learning and social environment by acquisition of additional technical, social and professional graduate-level skills. Post pandemic, bioscience students worry about the increased living costs and are strongly in favour of a mixture of face-to-face and blended learning approaches. Our results show that bioscience students can self-report poor mental health while developing resilience, indicating tailored support can aid in developing students’ resilience. Students have adjusted with ease to digital teaching provisions and now expect higher education institutions continue to offer both, face-to-face, and blended teaching, reducing the burden on students’ notably risen living costs.